Evaluation of the levels of IFN-gamma, IL-10 and Copper in children with Visceral Leishmaniasis. - kamil, Mais N.; Al-Najar, Sabah; Ghanim, Nahla (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Visceral Leishmaniasis( VL ) is a systemic infection of the reticulo- endothelial system that could affect the immune system and biochemical parameters like the concentration of Copper which may be significantly hanged . Objective: The study aims to evaluate the level of cytokines (INF- γ ,IL-10 ) and trace element (Cu ) in Visceral Leishmaniasis in children after diagnosis . patients and Methods: A total of 98 children, whose their ages ranged (6 menthes -5 years) were attending the Central Public Health Laboratory and Teaching Laboratories of Medical City, who were suspected to be infected with kala- azar, who were diagnosed by both IFAT technique and Rapid Kala-azar (r-K39) detecting test and trying to evaluate the level of cytokines (INF- γ , IL-10) by ELISA and concentration of ( Cu ) by Atomic Absorption Technique Results: The dipstick test ( r-K39) showed a high sensitivity of (92.1%) compared to IFAT (73.6%) with a specificity of 100% for both tests. Serum samples of 56 child with positive results in IFAT and rK39 test were used for the investigation of IL-10, IFN-γ. The mean levels of IL-10 (80.207±77.54 Pg/ml) and IFN- γ (5.426±4.599 IU/ml) were highly significant increased in patients compared to healthy controls. The mean level of serum Cu (171.54±10.37 μg/dl) in VL patients. Conclusions: This study showed that the ( r-K39) dipstick test could be more sensitive than IFAT technique in the diagnosis of VL with a specificity of 100 % for both test according to clinical diagnosis. Both IFN-γ & IL-10 were significantly increased in VL patients as compared to controls group. Copper concentration was significantly higher in VL patients than healthy controls.